THE RIGHT WAY TO PREACH ISLAM: THE CASE OF ALBANIA - Hysni Skura (Lafadz Jaya Publisher, 2023)
This paper explores the topic of preaching Islam in Albania, with a focus on the right way to do so. The study argues that religion is a set of principles sent by God to guide humanity towards happiness in this world and the next, and that a religion which does not produce results that enable man to become smarter leads to the loss of life values. Therefore, the preservation of faith, life, wealth, offspring and mind are the main objectives of religion. The study highlights that in the face of negative portrayals of Islam in the media, it is the duty of Muslim preachers to communicate the truth and inform their congregation about the true principles of Islam. The study uses Imam Ash-Shatibi's work to argue that the basic pillar of religion is the benefit of this life and the next, and therefore the study provides important insights into the role of preaching in contemporary society. The findings of this study have implications for the way in which Islam is practiced and preached in Albania and provide important guidance for those who wish to promote a positive and accurate understanding of Islam in the world today.